PENGARUH MOTIVATOR INSENTIF PADA KINERJA KARYAWAN DENGAN KEPERCAYAAN DIRI SEBAGAI PEMEDIASI - Dewi, Ida Sanjaya; Martono, S. (Management Analysis Journal, 2015)
The purpose of this study is to determine the influence of job satisfaction, work environment, and Organizational Citizenship Behavior on employee performance directly and indirectly that is mediated by Organizational Citizenship Behavior. The  population  in  this  study  were  all  employees  of  PT  Indonesian  Knitting Factory Semarang is 168 employees. Samples used is 117 employees. The method of  data  collection  by  quetionares. Data analysis using path analysis. The conclusion of this study are influence of job satisfaction and work environment on organizational citizenship behavior, the influence of organizational citizenship behavior  on employee performance and organizational citizenship behavior mediate the relationship job satisfaction and work environment on employee performance.